Green Bonds as Catalysts for Low-Carbon Financing Mobilization: Examining their Impact on Sustainable Development - Ragif Huseynov; Ramida Khalilova; Sanjay Taneja; Pawan Kumar; Ercan Özen (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study examines the crucial implication of green bonds in impede low-carbon investment and their subsequent power on sustainable development. Green bonds, being a financial tool, have gained growing awareness due to its capability to direct investments towards ecologically sustainable projects and initiatives. Green bonds have gained popularity to deal with sustainable development and climate change. It can finance credit to green projects, However, we must assess how successfully they fund low-carbon projects and how they affect sustainability. This research aims to explore the effectiveness of green bonds in magnetize funds that encourage low-carbon practice. This study investigates the societal and environmental impacts, market dynamics, and transparency issues surrounding green bonds, while examining their purpose in funding green projects, promoting credit inclusion, and advancing sustainability. A standardized survey has been conducted on 420 people of northern India, and questionnaire validated through pilot survey in form of reviews from experts and pre-testing. Smart PLS4 bootstrapping and PLS partial least square methods have been applied to find out desired results as per objectives of the research. The study's results highlight the positive impact of green bonds on sustainable development, emphasizing the importance of adherence to sustainability regulations, investor-focused management strategies, and financial inclusion, thereby encouraging key stakeholders across sectors to adopt more environmentally and ethically conscious practices. In addition, investment of green bonds in eco-friendly projects can improve a company's status and plead to awareness among society. Findings the prospective of low-carbon investment through green bonds might prompt strategist to consider set of laws.